2011
DOI: 10.1017/s0022029911000033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age at first lambing on reproductive and productive performance of Lacaune dairy sheep under an intensive management system

Abstract: The present study investigated the effect of age at first lambing (AFL) on the performance of Lacaune sheep under intensive management conditions. Records from 3088 maiden sheep from one farm, for the period 2005-2010, were classified into four experimental groups: group E (early) ewes with AFL ⩽390 d; group M (middle) with AFL of 391-450 d; group L (late) with AFL of 451-510 d; and group A (aged) with AFL ⩾511 d. The higher the number of lactations, the lower were the yield/lactation and yield/Day in Milk. Ew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
4
18
0
Order By: Relevance
“…There is good evidence that in most domestic species, nutrition is an important factor for the age and body weight of puberty [21]. The energy deficiency delays puberty and decreases animal fertility, body weight gain, and other productive parameters [22]. The present data showed that the ewes in supplemented group reached puberty at significantly earlier age than ewes of traditional feeding system of farmers.…”
Section: Discussionsupporting
confidence: 63%
“…There is good evidence that in most domestic species, nutrition is an important factor for the age and body weight of puberty [21]. The energy deficiency delays puberty and decreases animal fertility, body weight gain, and other productive parameters [22]. The present data showed that the ewes in supplemented group reached puberty at significantly earlier age than ewes of traditional feeding system of farmers.…”
Section: Discussionsupporting
confidence: 63%
“…Nevertheless, less than 200 ewes were removed from the data set because they were culled at an age of two or more years and without lambing records. Other populations provided similar performances such as the Rasa Aragonesa (528 days to 688 days; Gabiña, 1989) Hernandez et al, 2011). Smaller ages at first lambing were also reported in Finnish Landrace × Targhee (377 days) and Romanov × Targhee (365 days) flocks (Gallivan et al, 1993).…”
Section: Resultsmentioning
confidence: 69%
“…Descriptive study of the Lacaune lactation curve and biological interpretation As previously reported in Lacaune sheep (Hernandez et al, 2011) and Asaff sheep (Pollott and Gootwine, 2004), the mean milk yield per lactation and the length of lactation decreased with lactation number, that is, with the age of the sheep. The decrease between lactations 1 and 2 was slight, but it increased from lactation 2 onward.…”
Section: Discussionmentioning
confidence: 99%
“…This breed has become one of the world's high-yielding milk ovine breeds, with average daily milk yields of 1.59 l and a total milk yield of 270 l over a 165-day lactation period (Barillet et al, 2001). In Spain, our group has observed mean milk yields of 448 l/ewe in an intensively managed flock, with a mean lactation length of 238 days (Hernandez et al, 2011). Production of Roquefort cheese is strictly regulated by legislation of the European scheme of geographical indication named 'protected designation of origin'.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation